2017
DOI: 10.3389/fnana.2017.00089
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb Dynamic after Unilateral Focal Lesion of the Cervical Dorsal Corticospinal Tract with Endothelin-1

Abstract: Handedness is one of the most recognized lateralized behavior in humans. Usually, it is associated with manual superiority regarding performance proficiency. For instance, more than 90% of the human population is considered more skilled with the right hand, which is controlled by the left hemisphere, than with the left. However, during the performance of bimanual tasks, the two hands usually assume asymmetric roles, with one hand acting on objects while the other provides support, stabilizing the object. Tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In previous studies, we have shown the microinjections of N-Methyl-D-Aspartate (NMDA) into the ventral horn of rat spinal cord caused secondary white matter damage (WM) characterized by axonal degeneration, oligodendrocyte cell death, myelin impairment and intense inflammatory response [ 20 , 21 ]. We also reported that microinjections of endothelin-1 (ET-1) into the rat spinal cord also cause secondary degeneration of white matter tracts [ 23 ]. This phenomenon has also been observed by our group following microinjections of NMDA into the rat striatum [ 16 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have shown the microinjections of N-Methyl-D-Aspartate (NMDA) into the ventral horn of rat spinal cord caused secondary white matter damage (WM) characterized by axonal degeneration, oligodendrocyte cell death, myelin impairment and intense inflammatory response [ 20 , 21 ]. We also reported that microinjections of endothelin-1 (ET-1) into the rat spinal cord also cause secondary degeneration of white matter tracts [ 23 ]. This phenomenon has also been observed by our group following microinjections of NMDA into the rat striatum [ 16 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%